KETERAMPILAN PEMECAHAN MASALAH, SHARING TASK DAN JUMPING TASK MAHASISWA MENGGUNAKAN CASE METHOD DENGAN PENDEKATAN DEEP LEARNING - Yolanda, Yaspin; Fauziah, Anna (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
The research was carried out at PGRI Silampari University, Physics Education Study Program, from September to November 2024, based on the graduate output which required them to have problem solving competence, whether learning so far had built meaningfulness in learning (Deep Learning). This descriptive research uses a case-based learning method through lesson study for two cycles on campus involving 16 students as objects and 8 observers from fellow lecturers who observe the emergence of problem solving indicators, Sharing and Jumping Task indicators of students when solving cases on electrical circuits. Instruments include 1) sharing task and jumping task worksheets, 2) problem solving observation sheets, and 3) learning reflection sheets. To measure the increase in variables measured using N-Gain, the resulting data is then in the form of learning transcripts using TBLA (Transcript-based Lesson Analysis), the observation data is reduced and displayed graphically. Based on the results of open class observations for two cycles, it shows that there was an increase in students' problem solving skills during two cycles with an N-gain of 0.80 (high) so that the average problem solving skills of students were in the skilled category, while the Sharing and Jumping Task achievements of students with an N-Gain were of 0.88 (high) in the developing category. Furthermore, the results of peer lecturers' reflections and student reflections show that learning has adapted to learning needs (mindful), students think and are involved in the learning process (Meaningful) and students feel happy and satisfied in seeking deep understanding in a lesson (Joyful).